LQ45 Stock Recommendations with Fundamental Analysis Using the Simple Additive Weighting Method - Ramadiani Ramadiani; S. Saleh Al Idrus; Muhammad Labib Jundillah (Politeknik Pertanian Negeri Samarinda, 2024)
Shares are a sign of ownership of a person or entity in a company or limited liability company. Shares are in the form of a piece of paper that explains that the paper's owner is the owner of the company that issued the securities. In the Indonesia Stock Exchange (IDX) there are several kinds of stock indices, one of which is LQ45. It is known that until 2020 there were 2.48 million investors in the capital market. However, it should be noted that of the large number of investors, 85% to 90% of investors experience failure or loss. This happens because investors do not have adequate skills and knowledge in investing in stocks. Therefore, a system is needed that can assist in determining the selection of LQ45 stocks, namely a decision support system (DSS). This system was built web-based using the Simple Additive Weighting (SAW) method to determine the order of the most recommended stocks in the garden. This study uses 45 stocks as alternative data and 5 selection criteria, namely Return on Assets (ROA), Price to price-to-earnings ratio (PER), Price to Book Value (PBV), Net Profit Margin (NPM), and Debt to Equity Ratio (DER). The implementation of the SAW method on the system produces a sequence of LQ45 stock recommendations, namely Adaro Energy Indonesia as the best alternative with the highest preference value of 0.925.